Review of inpatient referrals for rheumatology: can we manage the patient on outpatient basis? - Srikanth Nandamoodi; Ramya Padala; Anupama Nandagudi; Anurag Bharadwaj (Future Healthcare Journal)
Background/Aims: With the increasing demand for inpatient beds on the NHS, we need to ensure that patients are being admitted only if necessary for long term conditions including rheumatic diseases. We wanted to determine whether the length of inpatient stays for patients could be reduced and whether they could have been managed differently on an outpatient basis.This study's aim is to evaluate the inpatient stay of patients with rheumatic diseases admitted to Basildon University Hospital. Methods: This is a retrospective review of medical records of 94 patients admitted at Basildon Hospital between May 2022 to July 2022. We evaluated patient details, including age, sex, their primary medical and rheumatological diagnoses, care they received, and the circumstances surrounding their hospital admission. We also tried to determine how many of these inpatients could be treated as outpatients. Results: Of 94 patients, 51% were males, their age ranged from 21 to 94 years (median 66 years). Commonest age group was 80–89 years comprising 22% of patients. Maximum number of inpatients stayed equally between 2–7 days and 15 to 30 days occupied 22 % each. The inpatient stay varied from 1 to 149 days with 13% patients staying more than 30 days. Most common indication of long-term hospital stays were social problems 38%. frailty 31% and infections 31%. The primary reason for admission was rheumatological in 42% of patients and medical in 55% of patients. There was no data available for 3%. The rheumatological reasons included GCA 32%, joint Swelling/pain 22%, vasculitis 14%, crystal arthropathy 14%, PMR 13% and drug reactions 5%. Medical reasons included infections 24%, falls 18%, neurology/strokes 14%, respiratory (Non-infectious & SOB) 11%, Oncology (meningioma/frontal lode tumour/RCC) 5% and others. Treatment from rheumatology team during admission was steroids 36%, DMARDS 23%, joint injections 10%, NSAIDS 2%, IVIG 3% etc. Rest of the patients (26%) were under investigation for diagnosis. After evaluation it was felt that 39% of these patients could have been managed on outpatient basis and 58% required inpatient care. Conclusion: This audit shows that 39% of admitted patients with rheumatological complaints can be managed on an outpatient basis. The concept of emergency or hot clinics as outpatient may be an efficient alternative for these patients.